The Association Between Interlimb Asymmetry and Athletic Performance Tasks: A Season-Long Study in Elite Academy Soccer Players. Issue 3 (27th March 2022) - Bishop, Chris; Read, Paul; Bromley, Tom; Brazier, Jon; Jarvis, Paul; Chavda, Shyam; Turner, Anthony
Abstract: Bishop, C, Read, P, Bromley, T, Brazier, J, Jarvis, P, Chavda, S, and Turner, A. The association between interlimb asymmetry and athletic performance tasks: A season-long study in elite academy soccer players. J Strength Cond Res 36(3): 787–795, 2022—The aims of this study were to determine the association between asymmetry and measures of speed and change of direction speed (CODS) performance throughout a competitive soccer season and, determine whether any observed changes in asymmetry were associated with changes in speed and CODS performance. Eighteen elite male under-23 academy soccer players performed unilateral countermovement jumps, unilateral drop jumps (DJ), 10- and 30-m sprints, and 505 CODS tests at pre, mid, and end of season. No significant relationships were evident during preseason or midseason between asymmetry and speed or CODS performance. Significant correlations were shown at the end of season between DJ height asymmetry and 10-m sprint time (ρ = 0.62; p = 0.006) and 505 time on the right limb (ρ = 0.65; p = 0.003). No significant correlations between changes in asymmetry and changes in speed or CODS were evident at any time point. Although numerous studies have reported associations between asymmetry and reduced athletic performance, it seems that these associations with speed and CODS do not track consistently over time. Thus, suggestions for the reduction of asymmetry that may indirectly enhance athletic performance cannot be made.